The frequency of disseminated intravascular coagulopathy in newly diagnosed adult patients with haematological malignancies attending Nanakaly Hospital in Erbil - Akram, Reving Rebar; Hassan, Kawa Muhammedamin (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Disseminated intravascular coagulation significantly contributes to the bleeding and thrombotic complications in patients with haematologic malignancies. This study was conducted to find out the incidence of disseminated intravascular coagulopathy in haematological malignancies before introduction of chemotherapy. Methods: A prospective case series study was performed at Nanakaly Hospital for Blood Diseases from April 30, 2011 to April 1, 2012. Seventy patients with different haematological malignancies were enrolled; they were assessed with clinical importance of global haemostatic laboratory tests. Results: Eighteen percent of studied patients had overt disseminated intravascular coagulopathy. The haemostatic measures were higher in overt disseminated intravascular coagulopathy cases than those with no evidence of disseminated intravascular coagulopathy cases (P < 0.001); and the highest incidence of disseminated intravascular coagulopathy cases was in acute promyelocytic leukemia's patients (77%, P = 039). Most of disseminated intravascular coagulopathy cases were clinically manifested with anemia, bleeding and rarely with thrombosis (100%, 69% and 7%, respectively). Conclusion: Disseminated intravascular coagulopathy is not uncommon in haematological malignancies before starting chemotherapy. Global haemostatic tests are helpful for diagnosis of disseminated intravascular coagulopathy side by side with clinical manifestations and medical history.